Motorcycle Anti-lock Braking System (ABS): Feasibility Study Towards Mandatory Installation in Malaysia - M. S. A. Khalid; K. A. A. Kassim; Z. M. Jawi; A. N. S. Z. Abidin; A. Hamzah; A. Roslan; M. H. Johari; M. S. Solah; S. A. S. M. Rahim; Z. H. Zulkipli (Journal of the Society of Automotive Engineers Malaysia, 2022)
In 2020, there were more than 4,000 traffic fatalities in Malaysia, with motorcycle riders accounting for more than 65% of those deaths. Among the causes of motorcycle collisions include single-vehicle wrecks, inability to avoid other cars, bad braking, and inability to control the motorbike while braking. ABS is one of the more current safety devices that might prevent these types of collisions. Therefore, this study aims to explore the feasibility of mandating Motorcycle ABS as a standard fitment for all motorcycles in Malaysia. The research methods include a literature analysis of previous studies, a comparison of countries that have controlled the installation, and a poll of Malaysian motorcycle riders regarding their perception of motorcycle ABS. According to previous research, motorcycle ABS might potentially save lives and reduce injuries by 26% to 39%, depending on the type of collision. With similar efficiency, it is predicted that over 1000 lives can be saved and over 100,000 injuries can be prevented in Malaysia. Small-engine motorcycles (below 250cc) are the most popular among Malaysian users; yet, the majority of small-engine motorcycles are not equipped with good motorcycle safety technology, especially ABS, when compared to large-engine motorcycles (250cc above). In addition, survey results indicate that most motorcyclists in Malaysia are knowledgeable about ABS and agree with its functionality and efficiency. Furthermore, most respondents agreed that Malaysia wanted to mandate the installation of ABS on all motorcycles, with 90% of respondents wanting it to be mandated immediately. Concerns were also raised that the regulation would not significantly affect the market price. In light of the effectiveness of anti-lock braking systems (ABS) in saving lives and preventing injuries, user awareness, understanding, and demand for ABS, as well as market readiness, it may be determined that Malaysia is able and prepared to regulate motorcycle ABS as a mandatory fitment to all motorcycle.